Comprehensive Analysis of Oil Sludge from The Absheron Peninsula to Solve Environmental Problems - Aliyev Goshgar; Aliyev Emin (BIO Web of Conferences)
The Absheron Peninsula, historically known for its oil production, is home to several key oil fields including Bibi-Eybet, Balakhani, Surakhani and Ramana. Decades of oil production have resulted in the accumulation of significant quantities of oil sludge, which poses significant environmental and economic challenges. The objective of this study is to conduct a comprehensive chemical analysis of oil sludge from these fields using an Agilent Technologies ICP-OES 5810 for elemental analysis and a Cary 630 FTIR for molecular characterization. The results provide valuable information on the composition of these sludges, which can facilitate more effective remediation and disposal strategies.